When Everything Else Fails: Radio Journalism During Hurricane Maria in Puerto Rico. (9th August 2019) - Nieves-Pizarro, Yadira; Takahashi, Bruno; Chavez, Manuel
ABSTRACT: In an era of over-reliance on online media technologies in disasters, this research examines the journalistic functions played by Puerto Rican AM radio workers during Hurricane Maria. Throughout the emergency there was total loss of electricity and communications, nonetheless local radio continued operations. This study is one of a few that explore journalistic practices during a disaster in the context of a Spanish-language media system. Through a qualitative analysis of in-depth interviews with radio workers, we found that in spite of having preparedness plans, the magnitude of the disaster led to improvization and the embracing of alternative journalistic roles. One of the main barriers was the inadequate technology for this particular context. Radio workers were also victims of the disaster and faced challenges in both their journalistic and first responder roles.